sebuah Pengaruh Pendekatan STEM Terhadap Kemampuan Berpikir Kritis Siswa : Meta Analisis - Betty Mizarwan; Yohandri; Usmeldi (Jurnal Penelitian Pendidikan IPA, 2026)
Indonesia's. STEM education is one method that may help students succeed in the modern world. This study set out to assess the quality of prior work that looked at how STEM education affected students' capacity for critical thinking. Level of education and learning model were the moderators taken into account in this research. In order to get quantitative data, the researchers used meta-analysis to determine the impact size of each study that was relevant. Journals acknowledged with an ISSN between 2020 and 2025 were the criterion used to look for national and international journals that have been researched by previous researchers. According to the impact size study of STEM education on students' critical thinking abilities, which was conducted across all educational levels and models, the findings were in the high category. This suggests that students' critical thinking abilities may be enhanced across all educational levels via the use of the STEM method in the classroom.